Paying Outsourced Labor: Direct Evidence from Linked Temp Agency-Worker-Client Data - Andres Drenik; Simon Jäger; Pascuel Plotkin; Benjamin Schoefer (Institute of Labor Economics (IZA), 2020)
We estimate how much firms differentiate pay premia between regular and outsourced workers. We study temp agency work arrangements where pay setting has previously escaped measurement because existing datasets do not report links between user firms (the workplaces where temp workers perform their labor) and temp agencies (their formal employers). We overcome this measurement challenge by leveraging unique administrative data from Argentina with such links. We estimate that temp agency workers receive 49% of theworkplace-specific pay premia earned by regularworkers in user firms: the midpoint between the benchmark for insiders (one) and the competitive spot-labor market benchmark (zero).
Keywords: J31; J53; L24; 330; outsourcing; temp agencies; non-standard work arrangements; rent sharing